Pembentukkan Tabel Morbiditas Penyakit Kronis Berdasarkan Angka Prevalensi - Khairul Alim; Gusmi Kholijah; Meinarisa Meinarisa (Limits: Journal of Mathematics and Its Applications, 2025)
A morbidity table is an important mathematical tool in health sciences and actuarial studies, providing an overview of disease rates in a population at a given time. This table offers information on the number of disease cases by age group, type of disease, or geographical region. The values from morbidity tables are used to compare disease rates between populations, evaluate the effectiveness of health programs, and predict future healthcare service needs. In the world of health insurance, morbidity tables play a crucial role in premium pricing calculations. By using specific morbidity tables, insurance providers can set premium prices that align with the conditions of the population being covered, preventing company losses due to premiums being set too low, while also ensuring that people do not feel burdened by excessively high premiums. Despite their importance, creating morbidity tables requires extensive research and large amounts of data. In Indonesia, accurately constructing morbidity tables is challenging due to its vast geographical diversity. Therefore, this study will use the prevalence rate of chronic diseases as an alternative. Prevalence rate is a statistical measure that describes the proportion of individuals in a population suffering from a specific disease at a given time. This approach simplifies data collection, especially since the government regularly releases prevalence data for certain diseases.